A functional MRI study of the influence of sleep deprivation on digital memory in human brain. - FAN Shuang-yi; LI Zhi-fang; SUN Bin-bin; YANG Wei-xi (Chinese Journal of Contemporary Neurology & Neurosurgery, 2013)
Background Working for long hours often leads to mental fatigue. There is evidence that mental fatigue is serious damage to cognitive function and behavior of the operator. Revealing the mechanism of continuous operation and sleep deprivation (SD) on cognitive function, will help to combat the fatigue caused by continuous operation and to improve capacity of operators. This functional magnetic resonance imaging (fMRI) study focused on the influence of sleep deprivation on digital memory in human brain. Methods Totally 6 healthy subjects underwent a digital memory encoding, maintenance and retrieval session during fMRI scanning before and after 48 h sleep deprivation. Results The digital memory test had the same error rate before and after sleep deprivation (P > 0.05, for all), but the reponse time of seven -number memory was longer after sleep deprivation (P = 0.005). During encoding trials decreased fMRI regions of significant activation between sleep control and sleep deprivation were in left parahippocampal gyrus Brodmann 30, left superior temporal gyrus Brodmann 42, left insular lobe Brodmann 41 and left frontal lobe Brodmann 6. During maintenance trials decreased fMRI regions of significant activation were at left superior temporal gyrus Brodmann 38, left middle temporal gyrus Brodmann 21, left parahippocampus and amygdaloid nucleus Brodmann 30, left middle frontal gyrus Brodmann 47, left lenticular nucleus and thalamus, right lenticular nucleus, left retrosplenial granular cortex Brodmann 30,right retrosplenial granular cortex Brodmann 30, bilateral cingulate gyrus Brodmann 24 and bilateral middle frontal gyrus, medial frontal gyrus Brodmann 6. During retrieval trials decreased fMRI regions of significantly positive activation were at bilateral hippocampus, right amygdaloid nucleus and inferior parietal lobule Brodmann 40, left precuneus Brodmann 19 and thalamus. Conclusion Different brain regions are activated at different stages of the digital memory to keep awake after sleep deprivation. The cerebral cortical and subcortical structures participated digital memory will be injured after 48 h of sleep deprivation.